Pengaruh Modal Kerja, Profitabilitas Dan Kebijakan Dividen Terhadp Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Makanan yang Terdaftar Di BEI: Pengaruh Modal Kerja, Profitabilitas Dan Kebijakan Dividen Terhadp Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Makanan yang Terdaftar Di BEI - Fadhilah, Nur; Nurnajamuddin, Mahfud; Umar, Nur Alam (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
This study was conducted with the aim of knowing the effect of working capital, profitability, and dividend policy on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange.This study uses a quantitative approach using secondary data. This research was conducted at the representative of PT. Indonesia Stock Exchange at the Indonesia Stock Exchange Gallery located at the Faculty of Economics and Business UMI JI. Urip Sumoharjo KM. 5 Makassar South Sulawesi, carried out for approximately 2 (two) months from August to September 2023. The population in this study were food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022, totaling 47 companies. Sample selection using purposive sampling technique with several predetermined criteria, the number of samples was 10 food and beverage sub-sector companies. Data and analyzed using the Structural Equation Modeling (SEM) program.The results of this study indicate that: (1) working capital has a significant effect on firm value; (2) profitability has no significant effect on firm value; (3) dividend policy has no significant effect on firm value.